Philosophical Thought Experiments, Intuitions, and Cognitive Equilibrium. - GENDLER, TAMAR SZAB (Midwest Studies In Philosophy (Wiley-Blackwell), 2007)
The article talks about philosophical thought experiments and their relation to intuitions and cognitive equilibrium. It explores three consequences of the suggestion that philosophical thought experiments exploit the discrepancy which lead to Charles Rollins' perplexity and David Hume's insight. Recent results from psychology and related disciplines supporting the author's interpretation are discussed.